Pengaruh Model Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa Materi Harmoni dalam Ekosistem Kelas V SD Negeri 06 Kelapa - Cici, Cici ayudia; Yurdayanti; Eka Wahyuningsih (JBES (Journal Basic Education Skills), 2025)
This research was motivated by students' difficulties in understanding the concepts of Harmony and Ecosystems, including difficulties in defining, giving examples, classifying concepts and difficulties in providing conclusions about the material taught by the teacher. This shows that students' critical thinking skills in working on questions are still low. The aim of the research was to determine the effect of using the problem based learning model on the critical thinking ability of students in Class V Harmony and Ecosystem material at SDN 06 Kelapa. The type of research is quantitative research with a pre-experimental design experimental method (the one-group pretest-posttest design). The subjects in this research were 28 class V students of SD Negeri 6 Kelapa. Data collection techniques and instruments include test questions and documentation. The analysis technique uses the paired samples t test. The results of the research show that there is an influence of the use of the problem based learning model on students' critical thinking skills in Class V Harmony and Ecosystems at SDN 06 Kelapa. This is proven by the t value of 16.884 which is greater than the t table of 1.703 and p = 0.000